2020
DOI: 10.1002/mds.28338
|View full text |Cite
|
Sign up to set email alerts
|

Shared Genetics of Multiple System Atrophy and Inflammatory Bowel Disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…And down-regulation of FOXO1 leads to over-production of Th17 cells and increased inflammatory responses 86 . DENND1B has been previously reported as one of the susceptibility gene regions that are associated with IBD(rs12740041) 87 especially CD and PBC((rs2488393)) 88 . However, our results found that DENND1B expression was significantly reduced in UC at the transcriptomic level.…”
Section: Discussionmentioning
confidence: 99%
“…And down-regulation of FOXO1 leads to over-production of Th17 cells and increased inflammatory responses 86 . DENND1B has been previously reported as one of the susceptibility gene regions that are associated with IBD(rs12740041) 87 especially CD and PBC((rs2488393)) 88 . However, our results found that DENND1B expression was significantly reduced in UC at the transcriptomic level.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, [11C]PBR28 positron emission tomography (PET), which visualizes the translocator protein expressed in glial cells, revealed a significant increase in the accumulation of lentiform nuclei and cerebellar white matter in MSA compared with PD, and both diseases could be differentiated with 83% sensitivity and 100% specificity [ 5 ]. Conversely, a genome-wide association study revealed a multifactorial overlap between MSA and inflammatory bowel disease, identifying three shared loci with reading variants upstream of the DENND1B and RSP04 genes and in an intron of the C7 gene, which has been implicated in various neuroinflammatory conditions [ 6 ].…”
Section: Advances In Understanding the Pathophysiologymentioning
confidence: 99%
“…Genome wide association studies (GWAS) identified several potentially interesting gene loci, including the FBXO47, ELOVL7, EDN1, and MAPT, but no association of SNCA and COQ2 variants with MSA [50]. Importantly, MSA and inflammatory bowel disease have been reported to share common genetics including common variants of the C7 gene supporting immune dysfunction in both disorders [51]. The current understanding is that certain genetic background may predispose to MSA.…”
Section: Evidence On the Cause Of Msa So Far -The Possible Interplay ...mentioning
confidence: 99%